The Effect of Snowball Throwing Method on Learning Outcomes of Grade XI Dance Students at SMA Negeri 12 Padang - Fuji; Fahendri, Intan (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2023)
This study aims to determine the differences in student learning outcomes taught using the snowball throwing method and student dance learning outcomes taught using conventional methods to improve student learning outcomes in cultural arts learning at SMA N 12 Padang. This type of research is quantitative, using experimental methods. The population in this study were 251 students of class XI SMA Negeri 12 Padang with a research sample of 2 classes, namely the experimental class (XI IPA 3) and the control class (XI IPA 4) with a total of 71 people, which were obtained based on average scores that were not much different and relatively the same standard deviation (assumed to be homogeneous) and normally distributed. The instrument used in this study was an objective test. The results showed that based on the t-test results, it was concluded that the alternative hypothesis (H1) was accepted at the 95% significance level and dk = (36+ 35) - 2 because tcount> ttable (2.07 > 1.67). In other words, the application of the snowball throwing method has an effect on the learning outcomes of Class XI SMA Negeri 12 Padang students. This can also be seen from the average difference in the scores of the experimental class (snowball throwing) being higher than the control class (conventional), which is 79.26> 74.47.